The Effect of the Implementation of E-Filing, Service Quality, and Taxpayer Awareness on Individual Taxpayer Compliance in Submitting Annual Tax Returns at KPP Pratama South Batam in 2019–2023 - Salsabila, Guliva; Ferdila; Richmayati, Maya (Jurnal sosial dan sains, 2025)
This study aims to examine the influence of e-filing implementation, service quality, and taxpayer awareness on individual taxpayer compliance at the KPP Pratama Batam Selatan. The method used is multiple linear regression analysis with data obtained through interviews, questionnaires, and documentation. The results show that e-filing implementation, service quality, and taxpayer awareness simultaneously have a significant impact on taxpayer compliance. The implementation of e-filing and good service quality significantly influences the increase in taxpayer compliance, while taxpayer awareness also contributes to enhancing compliance. This study suggests that the Directorate General of Taxes should continue to improve services, expand the use of e-filing technology, and educate the public on the importance of tax obligations.